GROWTH CHARACTERISTICS OF ASYSTASIA GANGETICA IN VARIOUS LEVELS OF UREA FERTILIZER - Suarna, I W.; Suryani, N. N.; Budiasa, K.M.; Saka Wijaya, I M. (Pastura, 2019)
Asystasia gangetica is a native plant that has the potential as a superior forage. The potential superiority of A. gangetica is not widely known by farmers in Bali. A study has been carried out with the aim to determine the growth and growth characteristics of A. gangetica as a forage. A completely randomized design with 5 levels of urea fertilizer treatment and 4 replications was carried out at Sesetan Denpasar research station. The results showed that the plant growth indicated by the variable number of branches, number of leaves, and shoot root ratio gave the highest yield on the level of urea fertilizer 50 kg ha -1 . Variable characteristics of plant growth such as Leaf Area Ratio, Leaf stem ratio, and plant length, have the same tendency, although they do not show significant differences. Observing the growth and growth characteristics of plants, it can be concluded that the use of urea fertilizer as much as 50 kg ha -1 provides the best growth and application of urea fertilizer exceeding 50 kg ha -1 will adversely affect the growth of A. gangetica. Keywords: A. gangetica, urea, growth, growth characteristics